2007
DOI: 10.1007/s11892-007-0032-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of type 2 diabetes: An update

Abstract: With the rising tide of the diabetes epidemic leading to increased morbidity and mortality (primarily from cardiovascular disease), together with failure to control the disease and its associated complications, prevention of diabetes appears to be the logical option for curbing this epidemic. Several trials have been completed, and others ongoing, using various strategies for diabetes prevention. In this review, we provide an update on diabetes prevention strategies, highlighting the rationale behind such inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…The HOPE (Heart Outcomes Prevention Evaluation) study showed that ramipril, 10 mg daily for 4.5 years, reduced the incidence of T2DM by 34% in non-diabetic individuals with CVD compared with placebo [16,39]. Similar glycemic protective effects were found with captopril (in the CAptopril Prevention Project, CAPPP), lisinopril (in the Antihypertensive and LipidLowering Treatment to Prevent Heart Attack Trial, ALLHAT) and losartan (in the Losartan…”
Section: Angiotensin-converting Enzyme Inhibitors and Angiotensin Recmentioning
confidence: 79%
See 4 more Smart Citations
“…The HOPE (Heart Outcomes Prevention Evaluation) study showed that ramipril, 10 mg daily for 4.5 years, reduced the incidence of T2DM by 34% in non-diabetic individuals with CVD compared with placebo [16,39]. Similar glycemic protective effects were found with captopril (in the CAptopril Prevention Project, CAPPP), lisinopril (in the Antihypertensive and LipidLowering Treatment to Prevent Heart Attack Trial, ALLHAT) and losartan (in the Losartan…”
Section: Angiotensin-converting Enzyme Inhibitors and Angiotensin Recmentioning
confidence: 79%
“…The discrepancy in findings between the DREAM trial and previous reports may be related to the difference in the study design and study population [16]. In the DREAM trial, diabetes prevention was a primary outcome and ramipril was compared with placebo.…”
Section: Angiotensin-converting Enzyme Inhibitors and Angiotensin Recmentioning
confidence: 82%
See 3 more Smart Citations